Formation of Communicative Competence in Children Entering Elementary School - Egorenko, T.A.; Bezrukavny, O.S. (Psihologiceskaâ nauka i obrazovanie (2007), 2017)
This article dwells upon the issues related to formation of meta-subject competencies’ communicative component in pupils during transfer to middle secondary school. The authors consider the approaches to notion “communicative competency” and specify its main components. The sensitivity of forming communicative competency in junior adolescence age is defined. The results of investigation into communicative competency is described. The article raises the question of the effect of psychological - pedagogical adaptation of students to the basic school on the formation of the communicative component metasubject competencies. The sample of 167 students from two educational complexes with intensive study of foreign languages Moscow. The conclusions are drawn about the need to implement a psychological and pedagogical program aimed at forming and developing communicative component of metasubject competencies at school. Обсуждается проблема метапредметных компетентностей и, в частности, их коммуникативный компонент. Рассматривается понятие «коммуникативная компетентность» и описываются методики исследования компонентов коммуникативной компетентности. Поднимается вопрос о влиянии психолого-педагогической адаптации учащихся к основной школе на формирование коммуникативного компонента метапредметных компетентностей. Описывается исследование степени развитости компонентов коммуникативной компетентности у учащихся пятых классов двух образовательных комплексов города Москвы (167 человек). Проводится качественный анализ полученных данных и делается вывод об уровне развития коммуникативной компетентности учащихся при переходе из начальной в основную школу. Особое внимание уделяется коммуникативным умениям и навыкам, развитие и формирование которых вызывает трудности у учащихся. Делается вывод о необходимости разработки психолого-педагогической программы по формированию и развитию коммуникативного компонента метапредметных компетентностей.